Shear strength of brick mortar interface for masonry in Lima city - Lavado, Luis (2019)
Masonry structures constitute a large proportion of the building inventory in Lima and in most cities in Peru, mainly because of their benefits in terms of low cost, good mechanical properties and easily worked. It was observed in the cyclic loading test of masonry walls carried out at CISMID that the modes of failures can be mainly generated by shear forces. Based on the previous information, it is known that diagonal cracking and slip of the mortar-brick joints are the dominant failure mechanisms of confined masonry walls.  In order to determine the mechanical behavior in the mortar-brick joint, an experimental program was carried out, by using industrial and handmade bricks. The test specimens were specifically designed to transmit pure shear along the bed joints under certain constant levels of compressive stress normal to the bed joint. The results of experimental shear tests are presented and discussed. It is then found a consistency between the behavior of masonry joints under shear with the Mohr Coulomb criterion. The shear failure capacity was influenced by the brick type, pre-compression load level and mortar type. It is also noticed in this experimental study that the pre-compressive stress normal to the bed joints significantly increase the shear strength of the mortar-brick joint.